Evaluation of Budget Implementation Performance at The Domestic Policy Strategy Agency, Ministry of Home Affairs - Stella Anastasia Wuka; Khasan Effendy; Ika Sartika (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to evaluate the budget implementation performance at the Domestic Policy Strategy Agency (Badan Strategi Kebijakan Dalam Negeri/BSKDN), Ministry of Home Affairs. The background of this research is based on the importance of effective, efficient, and accountable state budget management as part of good governance. The Budget Implementation Performance Indicator (IKPA) is used as the main instrument to assess the quality of budget execution, covering planning, implementation, and outcome aspects. This research employs a descriptive qualitative approach using the CIPP evaluation model (Context, Input, Process, Product) to obtain a comprehensive understanding of budget performance. Data were collected through document analysis, observation, and review of budget realization reports and IKPA achievements of BSKDN for the fiscal years 2022–2024. The results indicate that the budget implementation performance at BSKDN has improved over time, particularly in budget absorption, contractual spending, and output achievement, which have reached optimal levels. However, several indicators remain suboptimal, especially regarding revisions to DIPA Page III and the management of Cash Advances (UP) and Additional Cash Advances (TUP). Supporting factors include improved internal coordination, regulatory compliance, and better budget planning, while inhibiting factors involve dynamic planning changes and inefficiencies in operational cash management. This study recommends strengthening budget planning, enhancing financial management capacity, and optimizing internal control systems to improve IKPA scores sustainably. Therefore, budget implementation at BSKDN is expected to become more effective in supporting the achievement of organizational strategic goals and domestic governance policies.